2021
DOI: 10.23947/2334-8496-2021-9-3-301-317
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Action Research in Teachers’ Professional Development

Abstract: The challenges of contemporary education and teaching profession have resulted in an increased demand for the appropriate professional advancement and practice-based research. The action research is an approach that encourages teachers to manage and control their own work. This research was conducted with the purpose of being primarily beneficial for primary and secondary school teachers. The empirical research presented in this paper was based on the factor analysis, by which the research factors were extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
(11 reference statements)
0
1
0
Order By: Relevance
“…In view of the analyzed results, it can be concluded that preschool teachers highly assess their own effort for creating appropriate tools for working with children (higher level 34,6% and the highest level 13,1%) and the possibility of forming educational groups with appropriate number of children (higher . Preschool Teachers' Professional Training in the Field of Inclusive Education in The North of Kosovo and Metohija,International Journal of Cognitive Research in Science,Engineering and Education (IJCRSEE),11(1),[37][38][39][40][41][42][43][44][45][46][47][48][49][50] level 35,4% and the highest level 8,5%). Moreover, preschool teachers highly assessed advice from professional associates in everyday work with children (higher level 33,8% and the highets level 10,0%), in spite of the fact that they are not satisified with their support.…”
Section: Graph 6 Distribution Of Results Concerning the Items Of The ...mentioning
confidence: 99%
“…In view of the analyzed results, it can be concluded that preschool teachers highly assess their own effort for creating appropriate tools for working with children (higher level 34,6% and the highest level 13,1%) and the possibility of forming educational groups with appropriate number of children (higher . Preschool Teachers' Professional Training in the Field of Inclusive Education in The North of Kosovo and Metohija,International Journal of Cognitive Research in Science,Engineering and Education (IJCRSEE),11(1),[37][38][39][40][41][42][43][44][45][46][47][48][49][50] level 35,4% and the highest level 8,5%). Moreover, preschool teachers highly assessed advice from professional associates in everyday work with children (higher level 33,8% and the highets level 10,0%), in spite of the fact that they are not satisified with their support.…”
Section: Graph 6 Distribution Of Results Concerning the Items Of The ...mentioning
confidence: 99%
“…The study cross European project on "Inclusive early childhood education" pointed out the inclusive education outcomes in the centre, fed by (2) proximal inclusive education processes, and (3) struc-tural factors within the micro environment of the pre-school; and the more distant influences of (4) inclusive structural factors at community (or meso and exosys-tem levels), and (5) at national (or macro) levels (Paul, A. et al 2021). The need for training to enhance the knowledge and skills of preschool teachers in inclusive classrooms has been studied by many authors in many countries (Maria, K. et al, 2023, Kompirović, T. et al 2023.…”
Section: Discussionmentioning
confidence: 99%
“…An action research design was employed in this study to provide Science teachers who were pursuing their Master's degrees with an opportunity to gain knowledge in preparing a research project, express their perspectives on this process, and examine the outcomes of their engagement. Action research allows teachers to take control of their own work and obtain data that will benefit their methods (Osmanović Zajić, Mamutović, & Maksimović, 2021). It is valuable in this respect.…”
Section: Dıscussıonmentioning
confidence: 99%